If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5a(2a + 3) = 0 Reorder the terms: -5a(3 + 2a) = 0 (3 * -5a + 2a * -5a) = 0 (-15a + -10a2) = 0 Solving -15a + -10a2 = 0 Solving for variable 'a'. Factor out the Greatest Common Factor (GCF), '-5a'. -5a(3 + 2a) = 0 Ignore the factor -5.Subproblem 1
Set the factor 'a' equal to zero and attempt to solve: Simplifying a = 0 Solving a = 0 Move all terms containing a to the left, all other terms to the right. Simplifying a = 0Subproblem 2
Set the factor '(3 + 2a)' equal to zero and attempt to solve: Simplifying 3 + 2a = 0 Solving 3 + 2a = 0 Move all terms containing a to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2a = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 2a = 0 + -3 2a = 0 + -3 Combine like terms: 0 + -3 = -3 2a = -3 Divide each side by '2'. a = -1.5 Simplifying a = -1.5Solution
a = {0, -1.5}
| 18.6/6.2 | | -30E-6=0 | | -7(b-8)=112 | | 0.4+2.2=0.7x-0.2 | | 8x^2=104x | | 3(x-2)+7=5x-2(-1+x) | | 3(1+8x)=147 | | 2k(k+7)=-35 | | 2/3x=-2 | | LN(x)-LN(5)=-1 | | 5608/2 | | 8x=104x | | F(x)=7x^4-71x^3+102x^2+396x+216 | | 0=7x^4-71x^3+102x^2+396x+216 | | 6(-1-8n)=186 | | y=7x^4-71x^3+102x^2+396x+216 | | -15+x=-9 | | 4(-7n+8)=-192 | | 14x+8x^2=0 | | 14+8x^2=0 | | (9b-8)-2(4b+4)=-3 | | -2[4-(-2)+4(-3)]= | | 3(1-5v)=123 | | -8/3t^2+5/1/2t-8 | | 6(8-10)= | | 1/5x+1/2=-3 | | k+2/9=-8/5 | | 112y^2-116+24= | | -3(18-5x)+4=16 | | -4(4x+4)=-160 | | (x+4/6)=-20 | | -7(1+8n)=105 |